Conflict Tasks of Different Types Divergently Affect the Attentional Processing of Gaze and Arrow. (April 2018) - Fan, Lingxia; Yu, Huan; Zhang, Xuemin; Feng, Qing; Sun, Mengdan; Xu, Mengsi
The present study explored the attentional processing mechanisms of gaze and arrow cues in two different types of conflict tasks. In Experiment 1, participants performed a flanker task in which gaze and arrow cues were presented as central targets or bilateral distractors. The congruency between the direction of the target and the distractors was manipulated. Results showed that arrow distractors greatly interfered with the attentional processing of gaze, while the processing of arrow direction was immune to conflict from gaze distractors. Using a spatial compatibility task, Experiment 2 explored the conflict effects exerted on gaze and arrow processing by their relative spatial locations. When the direction of the arrow was in conflict with its spatial layout on screen, response times were slowed; however, the encoding of gaze was unaffected by spatial location. In general, processing to an arrow cue is less influenced by bilateral gaze cues but is affected by irrelevant spatial information, while processing to a gaze cue is greatly disturbed by bilateral arrows but is unaffected by irrelevant spatial information. Different effects on gaze and arrow cues by different types of conflicts may reflect two relatively distinct specific modes of the attentional process.